REDUPLIKASI BAHASA JAWA KLATEN - Albarokah, Sinthia; Faizah, Hasbah; Mustafa, M. Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to describe reduplicated form klaten Java language and Java language to describe the meaning of reduplication klaten. Reduplicated forms contained in the Java language Klaten is (1) looping whole, (2) looping portion, (3) looping combined with affix affixing process, (4) dwipura, (5) dwilingga, (6) dwilingga copy sound, (7) dwiwasana, (8) trilingga. Meaning reduplication Java language Klaten consist of (1) reduplications that contains the meaning 'many', 'all', 'whole' do against a common noun, (2) the reduplication which means 'resembles' or 'mock something', (3) reduplication stating the meaning of 'somewhat or a little', (4) which states reduplications meaning 'superlative'. This research was conducted in the village of Reed Anthology, District Seberida upstream Ibdragiri district. Data were obtained from six informants who have fulfilled the requirements that have been determined.Keywords: reduplication, dwilingga, dwipura